2019
DOI: 10.1002/jbm4.10256
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Phenotype Influences Bone Mineralization at Metastasis: A Study Using an In Vitro Prostate Cancer Metastasis Testbed

Abstract: In this study, two types of prostate cancer cell lines, highly metastatic PC‐3 and low metastatic MDA PCa 2b (PCa) were cultured on bone mimetic scaffolds to recapitulate metastasis to bone. A unique in vitro 3D tumor model that uses a sequential culture (SC) of human mesenchymal stem cells followed by seeding with cancer cells after bone formation was initiated to study the phenotype‐specific interaction between prostate cancer cells and bone microenvironment. The PCa cells were observed to be less prolific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…As demonstrated by previous experiments, microenvironment of distant organ can exert inhibitory effects on aggressive malignant cells at the early stage of tumor development [2]. However, the protective restraints of the microenvironment are overridden by pathological conditions such as stress, chronic in ammation [4].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…As demonstrated by previous experiments, microenvironment of distant organ can exert inhibitory effects on aggressive malignant cells at the early stage of tumor development [2]. However, the protective restraints of the microenvironment are overridden by pathological conditions such as stress, chronic in ammation [4].…”
Section: Introductionmentioning
confidence: 89%
“…Although surgical removal of primary tumors can extend or save life, it is well known that surgery itself may accelerate tumor metastasis [1]. Bone is the most common organ of metastasis especially in patients with breast and prostate cancer [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathologically, PCa bone metastasis is classified as an osteolytic disease. 101 Runx2 is a transcription factor that plays a key regulatory role in osteoblast differentiation. 102,103 DNA sequencing found that the receptor activator of nuclear factor kB ligand (RANKL) contains a Runx2 binding site in the promoter region.…”
Section: The αVβ3/runx2/rankl Pathway Is Closely Related To Osteolytimentioning
confidence: 99%